Postoperative cognitive dysfunction in elderly postcardiac surgery patients: progress in rehabilitation application research - Zhang, Zhen-Rong; Li, Yang-Zheng; Wu, Xiao-Qing; Chen, Wen-Jun; Xu, Jian; Zhao, Wei-Hua; Gong, Xiao-Yan (Frontiers in Rehabilitation Sciences, 2024)
Postoperative cognitive dysfunction (POCD) is a prevalent complication of the central nervous system in elderly patients following cardiac surgery. This review aims to provide an overview of the etiology, risk factors, diagnostic assessment, and rehabilitation strategies for cognitive dysfunction occurring after cardiac surgery. The pathogenesis of POCD after cardiac surgery includes cerebral microembolism, neuroinflammation, and cryptogenic strokes. Risk factors are associated with advanced age, diminished preoperative cognitive status, and anesthesia. Cognitive function screening tools used for pre- and postoperative assessments can detect changes in patients’ cognitive levels in a timely manner. The timely provision of appropriate rehabilitation methods, including cognitive function training, exercise training, transcranial direct current stimulation, and perioperative acupuncture, is crucial, with emerging technologies such as virtual reality playing an increasingly significant role. In conclusion, POCD is a common postoperative complication in elderly cardiac surgery patients, with age and reduced preoperative cognitive function being the primary risk factors. A comprehensive rehabilitation strategy can more effectively address postoperative cognitive dysfunction in patients.